Legal Uncertainty Regarding the Timeframe for Suspect Status Determination - Rosmaida Feriana, Gultom; Suparno, Suparno (Syntax Corporation Indonesia, 2024)
The study examines the legal uncertainties surrounding the time limits for determining suspect status within Indonesia's criminal justice system. The lack of clarity in the Criminal Procedure Code (KUHAP) regarding these time limits poses significant challenges to the human rights of suspects, particularly the constitutional guarantee of legal certainty. Without clearly defined timeframes for determining suspect status, investigations can extend indefinite period, leaving suspects uncertain whether their cases will proceed to prosecution or be dismissed. This situation subjects them to prolonged psychological, social, and economic strain and increases the risk of potential abuse of authority by investigators. Additionally, the study highlights the difficulties in establishing legal certainty concerning the time limits for suspect status and evaluates the necessary reforms to the Criminal Procedure Code to ensure fairness and safeguard the rights of suspects. One proposed solution is to implement a definitive time limit for the investigation process and the determination of suspect status, alongside strengthening internal and external monitoring mechanisms to mitigate the risk of authority misuse